Do e-commerce, e-wallet use, and store location affect purchasing intention? - Fazira Salsabila; Sri Ramadhani; Muhammad Ikhsan Harahap (Journal of Enterprise and Development (JED), 2023)
Purpose — The aim of this study is to examine the effect of e-commerce, e-wallet, and store location on consumer purchasing intention.Method — This research employed a quantitative research method, focusing on customers who had dined at Seblak Jeletet Medan. To gather data from a sample of 100 participants, a random sampling approach was used. The data collection process involved the distribution of questionnaires to all Seblak Jeletet Medan customers. Subsequently, the collected information underwent analysis through multiple linear regression.Result — The findings indicated that the utilization of e-commerce had a notable impact on consumer purchasing intention, e-wallet usage was also influential on consumer purchasing intention, and the geographical location of the store significantly affected consumer purchasing intention.Contribution — This research contributes to academia by precisely elucidating the impact of e-commerce utilization, e-wallet adoption, and store locations as pivotal factors affecting consumer purchasing intention